IMPLICATIONS OF PASSIVE SALT DIAPIR KINEMATICS FOR RESERVOIR SEGMENTATION BY RADIAL AND CONCENTRIC FAULTS - Stewart S.A. (My University, 2006)
Reservoirs associated with salt diapirs that are circular or elliptical in plan view can be segmented by radial faults, concentric faults, both or neither. Explanations for this variation are offered based on integration of fault kinematics, published studies and seismic examples. Strata around diapirs can be divided into three structural domains with characteristic fault styles. (1) Roof zone between the present day depositional surface and crest of a buried, inactive diapir. This zone is characterised by doming, radial faults and occasionally, conic graben. Doming is usually caused by differential compaction and increases with depth. (2) A steeply-dipping sheath of strata surrounds the diapir out to a distance of less than one diapir radius, recording near-surface diapir growth in poorly-lithified sediments. These contain early gravity slumps and late concentric extensional faults. Regional layer-bound polygonal fault systems form radial faults within approximately one diapir radius-the only significant radial faulting mechanism below the roof zone. (3) Diapir root zone of strata whose structural architecture records the diapirs' initiating mechanism, typically rim synclines or graben that detach on the salt source layer. Concentric faults at radial distances of a kilometre or more have been found only in root zone rim synclines and sheared sheath strata. These models and observations can assist seismic interpretation and structural model building in areas of poor geophysical imaging, for instance below overhanging salt. © 2006 Elsevier Ltd. All rights reserved.
Keywords: CONCENTRIC; DIAPIR; FAULT; RADIAL; SALT